2017
DOI: 10.1002/slct.201701162
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimalarial Evaluation of Piperidine- and Piperazine-Based Chalcones: Inhibition of Falcipain-2 and Plasmepsin II Hemoglobinases Activities from Plasmodium falciparum

Abstract: Never‐ending effort to develop new treatments for malaria, targeting the hemoglobin‐degradation in the food vacuole of the parasite is of particular interest because it appears to be critical for the erythrocytic stage parasite development. The Plasmodium aspartic proteinases plasmepsins and cysteine proteases falcipains have been shown to be the major hemoglobin‐degrading proteases and are proposed as the high priority drug targets by the World Health Organization for developing novel small molecules as inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Several studies have shown that the presence of an α,β-unsaturated carbonyl group confers the necessary reactivity to inhibit cysteine-proteases, specially cruzipain and falcipain-2. The data regarding α,β-unsaturated compounds showed strong in vitro inhibitory potency against cruzipain from T. cruzi and FP-2 from P. Falciparum, making them highly efficient in blocking the enzymatic activity in protozoan systems (Machin, Kantsadi, Vakonakis, 2019;Tiwari et al, 2017;Borchhardt et al, 2010;Yang et al, 2009;Santos, Moreira, 2007;Kunakbaeva, Carrasco, Rozas, 2003;Hans-Hartwig, Tanja, 1997).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Several studies have shown that the presence of an α,β-unsaturated carbonyl group confers the necessary reactivity to inhibit cysteine-proteases, specially cruzipain and falcipain-2. The data regarding α,β-unsaturated compounds showed strong in vitro inhibitory potency against cruzipain from T. cruzi and FP-2 from P. Falciparum, making them highly efficient in blocking the enzymatic activity in protozoan systems (Machin, Kantsadi, Vakonakis, 2019;Tiwari et al, 2017;Borchhardt et al, 2010;Yang et al, 2009;Santos, Moreira, 2007;Kunakbaeva, Carrasco, Rozas, 2003;Hans-Hartwig, Tanja, 1997).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…The two Plasmodium enzymes were plasmepsin II (PDB code 4cku) involved in haemoglobin metabolism by the parasite, and P. falciparum l-lactate dehydrogenase (pfLDH) (PDB code 1ldg) involved in glycolysis (or glucose metabolism of the parasite) [52,53,54]. There is a strong suggestion that haemoglobin digesting enzymes found in the food vacuole of the plasmodium and pfLDH are potential antimalarial chemotherapeutic targets for chloroquine and related aminoquionlones, anthraquinones and other oxidative phenolic compounds [55,56,57,58,59,60]. Besides, chloroquine has been found to bind to the cofactor (NADH) binding site of pfLDH acting as a competitive inhibitor [61].…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…The main strategy remains the increase of hydrophobic enzyme -ligand contact. 48 Due to the lack of quantitative accurate structural information about the pfFP2 active site subpockets efforts were oriented towards SAR studies of peptides and non peptidic scaffolds 49,50 but so far no integrated approach combining 3D-QSAR, PH4 and in silico screening has been reported and useful structural information is provided here.…”
Section: Analysis Of New Inhibitors From In Silico Screeningmentioning
confidence: 99%